The Observation of Natural Analogies and Their Use in Design - Darabos, Anita (International Journal of Engineering and Management Sciences, 2019)
According to, Thomas Heatherwick, who was an English architecture, ‘The biggest object is a building’. [1] Nature has phenomenal problem solving skills – ‘Nature knows it better’. It has an impact on us and on our subconscious.